Steel hybrid onshore wind towers installed with minimal effort: Development of lifting process. Issue 4 (August 2018) - Mohammadi, Mohammad Reza Shah; Richter, Carl; Pak, Daniel; Rebelo, Carlos; Feldmann, Markus
The total costs per produced kilowatt-hour for wind turbines depend significantly on the investment costs. Thereby, the tower is a relevant cost component, which depends on the chosen supporting structure, the material, and especially on the erection process. Here, an innovative erection process is presented in order to minimize the wind turbine installation, which leads to excluding the extra tall cranes for installing the wind turbines with hub heights over 180 m. In order to propose the innovative erection process, a new hybrid lattice/tubular supporting structure for the onshore wind turbines is designed. The connection component between the tubular part and lattice structure is proposed considering the support functionality for the new erection process. Furthermore, the building steps of the complete erection process are explained. The operational and the lifting loads on wind turbine supporting structure are estimated, and consequently, the erection process stages were analyzed. Finally, the finite element simulation are performed to specify the critical stresses in subcomponents of the supporting structure in each lifting stage and to show the feasibility of the erection process. Moreover, the most critical points and the stages are investigated and stress level in the supporting structure components is computed.